2003
DOI: 10.1002/tox.10102
|View full text |Cite
|
Sign up to set email alerts
|

Depuration kinetics and persistence of the cyanobacterial toxin microcystin‐LR in the freshwater bivalve Unio douglasiae

Abstract: We carried out uptake and depuration experiments in the laboratory to investigate the effects of temperature (15 degrees C and 25 degrees C) on the depuration kinetics and persistence of a cyanobacterial toxin, microcystin-LR (MCYST-LR), in a freshwater bivalve, Unio douglasiae. Bivalves were fed toxic Microcystis cells in the 15-day uptake experiment and nontoxic diatoms in the following 15-day depuration experiment. Each bivalve's hepatopancreas was lyophilized and extracted with a butanol:methanol:water sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 59 publications
4
54
0
Order By: Relevance
“…In the present study, temperature had close correlations both with intracellular toxin content, and with MCs content in snail hepatopancreas, suggesting the importance of water temperature on the MCs accumulation in snail hepatopancreas. Yokoyama and Park (2003) reported that Unio douglasiae accumulated much higher concentration (250740 mg/g DW) at 25 1C than that at 15 1C (130711 mg/g DW).…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, temperature had close correlations both with intracellular toxin content, and with MCs content in snail hepatopancreas, suggesting the importance of water temperature on the MCs accumulation in snail hepatopancreas. Yokoyama and Park (2003) reported that Unio douglasiae accumulated much higher concentration (250740 mg/g DW) at 25 1C than that at 15 1C (130711 mg/g DW).…”
Section: Discussionmentioning
confidence: 94%
“…Metabolic processes in living organisms, including biotransformation and detoxication, are strongly temperature dependent. Yokoyama and Park (2003) studied the kinetics of microcystin-LR depuration in freshwater bivalves. They revealed that significantly less toxin was eliminated from an organism incubated at 158C than at 258C, which indicated slower depuration rate of the toxin in winter.…”
Section: Blue Musselsmentioning
confidence: 99%
“…Pollution in marine bivalve mollusks can induce effects on the immune system and thus diseases susceptibility can be enhanced [62]. [63] studied the expression of Glutathione peroxidase (GPx) that is known to be directly involved in oxidative metabolism and reported that, oxygen is at the basis of oxidative metabolism, genes encoding enzymes involved in the cellular regulation of oxidative stress such as antioxidants are consequently expected to be regulated by hypoxia.…”
Section: Resultsmentioning
confidence: 99%